Return to elite football after the COVID-19 lockdown - Mohr, M.; Nassis, C. P.; Brito, J.; Randers, M. B.; Castagna, C.; Parnell, D.; Krustrup, P. (Managing Sport and Leisure, 2022)
The COVID-19 pandemic has changed the conditions for competitive football around the globe dramatically. Several competitions and leagues have been cancelled or postponed. Players have firstly been forced to training in solitude. In a second stage, players start training in small groups with strict contact restriction and return to competitive play might occur after only few weeks of normal team training preparation. These special circumstances are likely to impact football performance and injury risk in the upcoming competitions. Thus, clubs, coaching and medical staff, as well as players are challenged on the prioritization of fitness and performance, which easily can create several "catch-22-dilemmas". The present article presents views on fitness training, physical preparation and recovery during these uncommon conditions, and how elite football players can return to the competitive field well-prepared for post-crisis football endeavours around the world. Due to the multifaceted physiological demands in elite football, the long recovery requirements after match-play and an upcoming reality with many games within a short period, elite football players, managers and clubs may face extraordinary challenges associated with return to play under the current circumstances.